Arge pyracanthae n. sp. (Hymenoptera: Argidae) feeding on Pyracantha fortuneana in Hunan Province, China - Shinohara, Akihiko; Wei, Mei-Cai; Kiyoshi, Takuya (Zootaxa, 2015)
Arge pyracanthae Wei & Shinohara, n. sp. is described from Mt. Hupingshan, Hunan Province, China, including COI sequences from two specimens. Larvae are solitary external leaf feeders on Pyracantha fortuneana (Maxim.) H. L. Li (Rosaceae). Field observations and rearing experiments showed that this species has a multivoltine life cycle. This is the first record of an argid sawfly associated with Pyracantha.